2015
DOI: 10.1016/j.jhep.2015.07.034
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin C-terminal hydrolase 1: A novel functional marker for liver myofibroblasts and a therapeutic target in chronic liver disease

Abstract: Background & Aims-Ubiquitination is a reversible protein modification involved in the major cellular processes that define cell phenotype and behaviour. Ubiquitin modifications are removed by a large family of proteases named deubiquitinases. The role of deubiquitinases in hepatic stellate cell (HSC) activation and their contribution to fibrogenesis are poorly defined. We have identified that the deubiquitinase ubiquitin C-terminal hydrolase 1 (UCHL1) is highly induced following HSC activation, determined its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 36 publications
0
53
0
Order By: Relevance
“…Ubiquitin C-terminal hydrolase 1 (UCHL1), a deubiquitinase, is up-regulated following HSC activation, and promote their proliferation in CCl 4 and BDL mice [306]. Small molecule UCHL1 inhibitor, LDN-57444, attenuates PDGF-induced HSC proliferation by modulating phosphorylation of a cell cycle regulator, retinoblastoma protein (Rb).…”
Section: Mechanisms Of Hsc Activationmentioning
confidence: 99%
“…Ubiquitin C-terminal hydrolase 1 (UCHL1), a deubiquitinase, is up-regulated following HSC activation, and promote their proliferation in CCl 4 and BDL mice [306]. Small molecule UCHL1 inhibitor, LDN-57444, attenuates PDGF-induced HSC proliferation by modulating phosphorylation of a cell cycle regulator, retinoblastoma protein (Rb).…”
Section: Mechanisms Of Hsc Activationmentioning
confidence: 99%
“…Ubiquitin C-terminal hydrolase 1 (UCHL1, also known as PARK5/ PGP9.5), is a DUB responsible for removing ubiquitin or polyubiquitin from target proteins (7,8). It is highly dysregulated and plays critical roles in several disorders, including tumors, neurodegenerative diseases, and liver fibrosis (8,9). One study reported that UCHL1 influences skeletal muscle development and function.…”
Section: Introductionmentioning
confidence: 99%
“…According to Wilson et al, UCHL1 'can also interact and stabilize cell proteins such as b catenin, and activate kinases such as CDK4 without the requirement for its enzymatic activity' that has both hydrolase and ligase activities [48]. According to Zhang et al [49]: 'UCHL1 is expressed predominantly in the brain and neuroendocrine systems, and accounts for 1-2% of total brain soluble proteins'.…”
Section: Discussionmentioning
confidence: 99%
“…Concentrations of UCHL1 in the blood plasma of children with appendicitis g1, before surgery, g2, 24 h after surgery and g3, 72 h after appendectomy; ctrl 5 control group. et al [48] shows that: 'pharmacological inhibition of UCHL1 blocks hepatic stellate cells proliferation and when administered in vivo acts in a therapeutic way to block progression of established fibrosis despite continued liver injury'. Despite many functions identified so far, there are no data available in the literature on the correlation of expression of UCHL1 and inflammation.…”
Section: Discussionmentioning
confidence: 99%